IMPLEMENTASI DIGITAL MARKETING BERBASIS MARKETPLACE DAN MEDIA SOSIAL DALAM MENINGKATKAN KINERJA UMKM BGS TEXTILE - Muhammad Bagas Saputra; Dendy Kurniawan; Irdha Yunianto; Erinda Anasia Agustin (Jurnal Padamu Negeri, 2026)
This community service activity aims to implement digital marketing based on marketplace and social media to improve the performance of BGS Textile MSMEs. The main problem faced by the partner is the lack of optimal utilization of digital technology in marketing activities, particularly in managing marketplace platforms and social media. The method used in this study is a participatory training and mentoring approach, which includes initial observation, digital marketing training, platform usage practice, as well as evaluation and monitoring. The results show that MSME actors are able to create and manage an online store on the Shopee platform, organize digital product catalogs, and utilize available promotional features. In addition, there is an improvement in the ability to design promotional content and use social media as a branding tool. However, the improvement in business performance, particularly in terms of sales, has not been significant at the initial stage of implementation. Overall, this activity successfully establishes a foundation for information system-based digital marketing that can be further developed to enhance MSME competitiveness in the digital era.